2006
DOI: 10.1002/adsc.200600367
|View full text |Cite
|
Sign up to set email alerts
|

Gold Catalysis: Dihydroisobenzofurans and Isochromanes by the Intramolecular Furan/Alkyne Reaction

Abstract: A series of furyl alcohols and homofuryl alcohols was synthesized by reduction of furfurals or reaction of furyllithium compounds with epoxides and subsequent propargylation. The gold-catalyzed cycloisomerization of these products furnished dihydroisobenzofurans and isochromanes. Crystal structure analyses proved the sequence of the substituents for both classes of products. Unsaturated dicarbonyl compounds as side-products show the mechanistic relationship to the analogous platinum-catalyzed reactions. Neithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 34 publications
0
40
0
1
Order By: Relevance
“…Mechanistic insight was obtained from a series of experiments: (a) 18 O labeling studies indicated that the oxygen atom of the furan ring migrates intramolecular to become the phenolic oxygen atom [17]. (b) Side products observed in less selective platinum catalysed reactions indicated that the reaction proceeds via a carbenoid species 9 (scheme 2), similar side products were observed in gold catalysed conversion only recently [25]. (c) Arene oxides 11 (scheme 2) could be observed as intermediates and trapped by a Diels-Alder reaction [22].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Mechanistic insight was obtained from a series of experiments: (a) 18 O labeling studies indicated that the oxygen atom of the furan ring migrates intramolecular to become the phenolic oxygen atom [17]. (b) Side products observed in less selective platinum catalysed reactions indicated that the reaction proceeds via a carbenoid species 9 (scheme 2), similar side products were observed in gold catalysed conversion only recently [25]. (c) Arene oxides 11 (scheme 2) could be observed as intermediates and trapped by a Diels-Alder reaction [22].…”
Section: Introductionmentioning
confidence: 81%
“…This synthesis is based on a sequence which included the condensation of a furfural derivative 1 and an amino acid derivative 2, the catalytic asymmetric hydrogenation of 3 and the goldcatalysed cycloisomerization to give the phenol 6 [17][18][19][20][21][22][23][24][25][26][27][28][29] as key steps.…”
Section: Introductionmentioning
confidence: 99%
“…Both 3a and 3b also catalysed the more challenging cyclisation of w-alkynylfuran 7, but required a catalyst loading of 0.25 mol%, corresponding to TONs of 240 and 280 for 3a and 3b, respectively. For comparison, AuCl 3 catalysed the same cyclisations but required 5 mol% loading to achieve 64 and 71% conversion to 6 and 8, respectively, which corresponds to turnover numbers of 13 and 28, [12] and highlights the efficiency of the gold(I)/KITPHOS systems (entries 5 and 6). Moreover, with 4a only slightly better results were obtained (71%, entry 7), while 4b had a much lower activity (10%, entry 8).…”
mentioning
confidence: 96%
“…Complexes 3a and 3b were each tested in the cyclisation of w-alkynylfurans [12] (entries 1-8), the cyclisation of 2-alkynylaryl epoxides [13] (entries 9-16) and N-propargylcarboxamides [14] (entries 17-24) as well as the intramolecular hydroalkoxylation (entries 25-30) and hydroxycarboxylation (entries 31-36) of allenes. [15] Gratifyingly, 3a and 3b both proved to be highly efficient cata- lysts for the cycloisomerisation of 5 to give the phenol 6 in conversions of 90 and 95%, respectively, with 0.05 mol% catalyst, which corresponds to turnover numbers of 1800 and 1900, respectively (entries 1 and 2).…”
mentioning
confidence: 99%
“…The organic layer was washed with H 2 O, dried over Na 2 SO 4 , filtered, and the solvent removed in vacuo to yield known 5a (78%). 6 1 H NMR (300 MHz, CDCl 3 ): d = 4.19 (br s, 1 H), 5.80 (s, 1 H), 6.35 (dd,J = 3.3,1.9 Hz,1 H),6.54 (dd,J = 3.7,1.7 Hz,1 H),6.40 (d,J = 3.3 Hz,1 H),7.25 (dd,J = 3.7,0.8 Hz,1 H),7.37 (dd,J = 1.8,0.8 Hz,1 H),7.61 (dd, J = 1.7, 0.8 Hz, 1 H).…”
Section: 2-di(furan-2-yl)-2-hydroxyethanon (5a)mentioning
confidence: 99%